SALURAN PEMASARAN BUAH JERUK NIPIS DI KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Nurmaya, Nurmaya; Rosmalah, Sitti; Harianti, Harianti; Tao, Haerudin (Fakultas Pertanian, Universitas Janabadra, 2024)
Marketing is the most important thing so that the distribution of lime fruit can be spread to the end consumer. This study aims to identify the marketing channels for lime fruit in Landono District, South Konawe Regency. In addition, it describes the efforts of farmers to face the risks of marketing lime. The location of the study was determined intentionally (purposively), namely in Watabenua Village, Wonua Morini Village and Tridana Mulya, Landono District, South Konawe Regency. Data collection was carried out by interview method to the main respondents in both marketing channels. This study is qualitative. The results of the study show that: first, the marketing channels formed in the research area consist of two, namely: the first channel: farmers-consumers and the second channel: farmers → middlemen → distributors → consumers. Second, farmers in marketing activities carry out management functions to deal with the emergence of production risks and price risks in the lime marketing channel.